English for international negotiations : - Rodgers, Drew (St. Martin’s Press, 1997)
English for International Negotiations is built around the case-study method, and covers a variety of negotiation situations set in more than twenty countries around the world. The Student's Book addresses issues such as cultural sensitivity, the need for a common language at the negotiating table, and other factors that influence success and failure in negotiation.